Art and Womanhood in Fin-de-Siecle Writing : the Fiction of Lucas Malet, 1880-1931. - Delyfer, Catherine (Gender and genre., 2015)
Lucas Malet is one of a number of forgotten female writers whose work bridges the gap between George Eliot and Virginia Woolf. Malet's writing was intrinsically linked to her passion for art. This is the first book-length study of Malet's novels.